2019
DOI: 10.3168/jds.2019-16438
|View full text |Cite
|
Sign up to set email alerts
|

Individual characteristics in early life relate to variability in weaning age, feeding behavior, and weight gain of dairy calves automatically weaned based on solid feed intake

Abstract: Little is known about factors affecting individual variability in weaning age, feeding behavior, and growth of dairy calves. The objectives of this study were to (1) describe early-life individual characteristics of dairy calves and how these relate to weaning age, feeding behavior, and performance during the first 15 wk of age, and (2) to identify which of these individual characteristics predict weaning age of calves automatically weaned based on solid feed intake. Early-life characteristics of calves (n = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 38 publications
3
38
0
2
Order By: Relevance
“…Individual behavioural responses to different novel or challenging situations were assessed using three traditional tests (open field, novel human, and a novel object tests 15 ), and a novel food (food neophobia) test. In line with our previous work 5,25 , and other studies in dairy calves 26,38 , we anticipated these tests to identify boldness and exploratory personality traits. These tests were carried out individually in a test pen that was identical to the home pen except that access to the feeding equipment was prevented using plywood.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Individual behavioural responses to different novel or challenging situations were assessed using three traditional tests (open field, novel human, and a novel object tests 15 ), and a novel food (food neophobia) test. In line with our previous work 5,25 , and other studies in dairy calves 26,38 , we anticipated these tests to identify boldness and exploratory personality traits. These tests were carried out individually in a test pen that was identical to the home pen except that access to the feeding equipment was prevented using plywood.…”
Section: Methodsmentioning
confidence: 63%
“…latency to approach novel food) and exploratory (e.g. time spent inspecting and eating the novel food) personality traits that have previously been identified in other novelty tests in dairy calves 5,25,26 . Indeed, a novel food test has been employed in a number of other species as a means of measuring these personality traits (fish: 27,28 ; birds: [29][30][31] primates: 32,33 ).…”
mentioning
confidence: 81%
“…Several studies have shown interindividual variability in milk intake among dairy calves before and after weaning (Rosenberger et al, 2017;Dennis et al, 2018), which likely contributes to the interindividual variability in weight gains (e.g., 0.1-1.6 kg/d; Soberon et al, 2012) or weaning age (Neave et al, 2019) observed across studies. Also, interindividual variability was reported in feeding behavior such as drinking speed and the number of rewarded and unrewarded visits to the milk feeder among preweaning calves (de Passillé and Rushen, 2012;Korst et al, 2017;Gerbert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Usually, calves start consuming small amounts of solid feed around 14 days of age [19]. Neave et al [30,31] observed a large variation in the age (range from 4 to 41 days of age in the study in 2018; range from 18 to 75 days of age in the study in 2019) when calves first found and began to consume starter. Some of our experimental calves started to consume the starter diet as early as 6 days of age, and the artificial grooming group tended to have a higher proportion of starter-diet-consuming calves.…”
Section: Starter Diet Ingestionmentioning
confidence: 99%
“…There is evidence that calves that were more exploratorily active began to consume starter at an earlier age, showed greater starter dry matter intake, and had higher overall average daily weight gain [30]. There is also a positive association between the level of exploratory activity and preweaning of calves [31]. Therefore, it seems likely that artificial grooming treatment might accelerate the solid food intake of calves by increasing their activity level.…”
Section: Starter Diet Ingestionmentioning
confidence: 99%